Flexible Electronics: Broadband Light Out‐Coupling Enhancement of Flexible Organic Light‐Emitting Diodes Using Biomimetic Quasirandom Nanostructures (Advanced Optical Materials 2/2015). Issue 2 (February 2015) - Wang, Rong; Xu, Lu‐Hai; Li, Yan‐Qing; Zhou, Lei; Li, Chi; Ou, Qing‐Dong; Chen, Jing‐De; Shen, Su; Tang, Jian‐Xin
<x xml:space="preserve">Abstract</x> On page 203, Y.‐Q. Li, S. Shen, J.‐X. Tang, and co‐workers demonstrate a wavelength‐independent light extraction scheme using nanoimprinted biomimetic quasi‐random nanostructures to simultaneously enhance light out‐coupling without color distortion and minimize the ohmic losses for multicolored, flexible organic LEDs. A superior color stability over the whole visible light range for wide viewing angles is realized due to the broad periodicity distribution and randomized emission directionality. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>